Effect of Tamoxifen on the Risk of Osteoporosis and Osteoporotic Fracture in Younger Breast Cancer Survivors: A Nationwide Study - Lee, Jihyoun; Alqudaihi, Heba M.; Kang, Michael Seungcheol; Kim, Jisun; Lee, Jong Won; Ko, Beom Seok; Son, Byung Ho; Ahn, Sei Hyun; Lee, Jong Eun; Han, Sun Wook; Kim, Zisun; Hur, Sung Mo; et al. (Frontiers in Oncology, 2020)
Background Although international guidelines recommend bone screening for premenopausal breast cancer patients taking adjuvant tamoxifen, the effects of tamoxifen on osteoporosis and related risks remain controversial. The objective of this study was to investigate the incidence of and risk factors for osteoporosis and osteoporotic fractures in younger breast cancer patients. Methods A nationwide retrospective cohort study was conducted using South Korea Health Insurance Review and Assessment Service claims data. The rates of osteoporosis and osteoporotic fracture were calculated as incident cases per person-year and disease-free probability rates were analyzed with the Kaplan-Meier method. To identify risk factors for osteoporosis and osteoporotic fracture, a multivariable Cox proportional hazard regression model was applied. Results From January 2009 to December 2014, a total of 47,649 breast cancer patients were included. The incidence rates of osteoporosis and osteoporotic fracture were 23.59 and 2.40 per 1000 person-years, respectively. In the overall population, tamoxifen was significantly associated with a decreased risk of osteoporosis and osteoporotic fractures 0.76). However, tamoxifen was not associated with the risk of osteoporosis (HR 1.24, CI 0.85 – 1.82) and osteoporotic fracture (HR 8.15, CI 0.36 – 186.70) in patients under age 40. In the 40-49 year subgroup, tamoxifen significantly decreased the risk of osteoporosis (HR 0.74, CI 0.65 – 0.84) and osteoporotic fracture (HR 0.49, CI 0.31 – 0.76). Conclusions Tamoxifen is not associated with an increased risk of osteoporosis and osteoporotic fracture in premenopausal breast cancer patients. Tailored screening strategies for breast cancer survivors with different osteoporosis risks are needed.